An Ultra-High-Throughput Screen for Catalytic Inhibitors of Serine/Threonine Protein Phosphatases Types 1 and 5 (PP1C and PP5C). (January 2017) - Swingle, Mark; Volmar, Claude-Henry; Saldanha, S. Adrian; Chase, Peter; Eberhart, Christina; Salter, Edward A.; D'Arcy, Brandon; Schroeder, Chad E.; Golden, Jennifer E.; Wierzbicki, Andrzej; Hodder, Peter; Honkanen, Richard E.
Although there has been substantial success in the development of specific inhibitors for protein kinases, little progress has been made in the identification of specific inhibitors for their protein phosphatase counterparts. Inhibitors of PP1 and PP5 are desired as probes for research and to test their potential for drug development. We developed and miniaturized (1536-well plate format) nearly identical homogeneous, fluorescence intensity (FLINT) enzymatic assays to detect inhibitors of PP1 or PP5. The assays were used in an ultra-high-throughput screening (uHTS) campaign, testing >315, 000 small-molecule compounds. Both assays demonstrated robust performance, with a Z′ of 0.92 ± 0.03 and 0.95 ± 0.01 for the PP1 and PP5 assays, respectively. Screening the same library with both assays aided the identification of class inhibitors and assay artifacts. Confirmation screening and hit prioritization assays used [ 32 P/ 33 P]-radiolabel protein substrates, revealing excellent agreement between the FLINT and radiolabel assays. This screening campaign led to the discovery of four novel unrelated small-molecule inhibitors of PP1 and 30 related small-molecule inhibitors of PP5. The results suggest that this uHTS approach is suitable for identifying selective chemical probes that inhibit PP1 or PP5 activity, and it is likely that similar assays can be developed for other PPP-family phosphatases.